YUNG DE PRÉVAUX, Aude. Jacques e Lotka: uma história da Resistência. - Campos, Maria Consuelo Cunha (Revista Estudos Feministas, 2003)
YUNG DE PRÉVAUX, Aude. Jacques e Lotka: uma história da Resistência.